PENERAPAN MEDIA MONOSA (MONOPOLI BAHASA) BERBASIS KEMANDIRIAN DALAM PEMBELAJARAN DI SEKOLAH DASAR - Suciati, Sri; Septiana, Ika; Untari, Mei Fita Asri (Universitas Pendidikan Indonesia, 2015)
This research applying learning media Monosa (monopoli bahasa) based on the child's independence in the classroom. Research and development (RnD) aims to describe the prototype instructional media monosa independence based on elementary students. Based on the analysis to the needs of the draft obtained monosa products, namely media that not only disposable and made of material that is waterproof, medium-sized and can be placed on the table. Learning media containing material that is diverse and covers all aspects of language skills. Media with images that vary according to the material Indonesian elementary school fourth grade. Based on the validation results showed that the learning media Monosa fit for use. It can be used by learners, learning media can also create an atmosphere of fun and do not saturate because the learning is done with playing. After revisions based test experts, media monosa tested in small classes. Monosa showed that the media has the effectiveness, the efficiency, and has appeal to users. Based on observations made during the study, the media is capable of providing meaningfulness in learning, which enhances the value of the character's ability to work together, sportsmanship, the activity of individual students, student independence, critical thinking, and caring.Keywords: application, media monopoly of the language, elementary students.